Cost benefit analysis for green hydrogen production from treated effluent: The case study of Oman - Barghash, Hind; Al Farsi, Arwa; Okedu, Kenneth E.; Al-Wahaibi, Buthaina Mahfoud (Frontiers in Bioengineering and Biotechnology, 2022)
Recently, the management of water and wastewater is gaining attention worldwide as a way of conserving the natural resources on the planet. The traditional wastewater treatment in Oman is such that the treated effluent produced is only reused for unfeasible purposes such as landscape irrigation, cooling or disposed in the sea. Introducing more progressive reuse applications can result in achieving circular economy by considering treated effluent as a source of producing new products. Accordingly, wastewater treatment plants can provide feedstock for green hydrogen production processes. Involvement of the wastewater industry in the green pathway of production scores major points in achieving decarbonization. In this paper, the technical and economic feasibility of green hydrogen production in Oman was carried out using a new technique that would help explore the benefits of the treated effluent of the wastewater treatment in Oman. The feasibility study was conducted using the Al Ansab sewage treatment plant in the governate of Muscat in Wilayat (region), Bousher. Results have shown the revenue from Al Ansab STP conventional case is 7.02 million OMR/year, while sustainable alternatives to produce hydrogen from Proton Exchange Membrane (PEM) electrolyzer system for two cases with capacities of 1,500 kg H2/day and 50,000 kg H2/day, are 8.30 million OMR/year and 49.73 million OMR/year, respectively.